PERTUMBUHAN DAN HASIL SELEDRI (Apium grafeolens L.) PADA MEDIA PASIR SETELAH DIBERIKAN GANDASIL D DAN ATONIK - Muhammad Riadh Uluputty (Agrologia, 2015)
Improvement growth and yield of celery in a polybag with sand media needs fertilizer and growth hormones tostimulate plant growth. The aim of this study was to determine the effect Gandasil D and Atonik on the growth andyield of celery (Apium grafeolens L.) grown in sand in polybag. The experiment was arranged in FactorialRandomized Block Design to tested liquid fertilizer Gandasil D concentration (without and with 1.0 g/L, 1.5 g/Land 2.0 g/L) and growth hormone Atonik concentrations (without and with 1.5 mL/L, and 2.0 mL/L). The resultsshowed that only liquid fertilizer Gandasil D which showed a significant effect on the growth of  celery.Application of Gandasil D at a concentration of 2.0 gwas/L  the best concentration to increase plant height,number of tillers, leaf number and fresh shoot weight.